EKSISTENSI ASAS PROPORSIONALITAS DALAM KONTRAK PENANAMAN MODAL - Ambarawan, Feri; Wiryawan, I Wayan; Darma Kusuma, A.A. Gde Agung (Kertha Wicara : Journal Ilmu Hukum, 2013)
The existance of proporsionalities principle in capital investmentagreement is wthin pre-agreement step, proporsionalities principle opensnegotiation among parties to interchange rights and duties, in fair, information step of agreement, this principle guarantees the equal rights andmakes free in controlling rights and duties proportions, in agreementimplementation proporsionalities principle guarantees for implementationof rights and duties interchange distribusion in accordance with proportionagreed and in case failure and dispute take place, so proporsionalitiesprinciple must be assesed proportinally about failure taken place andstresses on provement burden among parties.
Keywords: proporsionalities principle, agreement